Factors predicting prognosis and recurrence in patients with esophago-gastric adenocarcinoma and histopathological response with less than 10 % residual tumor - Ott, Katja; Blank, Susanne; Weichert, Wilko; Roth, Wilfried; Peters, Leila; Stange, Annika; Jäger, Dirk; Büchler, Markus W. (Langenbeck's archives of surgery, 2012)
PurposeNeoadjuvant treatment is an accepted standard approach for treating locally advanced esophago-gastric adenocarcinomas. Despite a response of the primary tumor, a significant percentage dies from tumor recurrence. The aim of this retrospective exploratory study from two academic centers was to identify predictors of survival and recurrence in histopathologically responding patients.MethodsTwo hundred thirty one patients with adenocarcinomas (esophagus: n = 185, stomach: n = 46, cT3/4, cN0/+, cM0) treated with preoperative chemotherapy (n = 212) or chemoradiotherapy (n = 19) followed by resection achieved a histopathological response (regression 1a: no residual tumor (n = 58), and regression 1b < 10 % residual tumor (n = 173)).ResultsThe estimated median overall survival was 92.4 months (5-year survival, 56.6 %) for all patients. For patients with regression 1a, median survival is not reached (5-year survival, 71.6 %) compared to patients with regression 1b with 75.3 months median (5-year survival, 52.2 %) (p = 0.031). Patients with a regression 1a had lymph node metastases in 19.0 versus 33.7 % in regression 1b. The ypT-category (p < 0.001), the M-category (p = 0.005), and the type of treatment (p = 0.04) were found to be independent prognostic factors in R0-resected patients. The recurrence rate was 31.7 % (n = 66) (local, 39.4 %; peritoneal carcinomatosis, 25.7 %; distant metastases, 50 %). Recurrence was predicted by female gender (p = 0.013), ypT-category (p = 0.007), and M-category (p = 0.003) in multivariate analysis.ConclusionResponse of the primary tumor does not guarantee recurrence-free long-term survival, but histopathological complete responders have better prognosis compared to partial responders. Established prognostic factors strongly influence the outcome, which could, in the future, be used for stratification of adjuvant treatment approaches. Increasing the rate of histopathological complete responders is a valid endpoint for future clinical trials investigating new drugs.
Gesehen am 05.04.2018